Transient non-integrative expression of nuclear reprogramming factors promotes multifaceted amelioration of aging in human cells - Sarkar, Tapash Jay; Quarta, Marco; Mukherjee, Shravani; Colville, Alex; Paine, Patrick; Doan, Linda; Tran, Christopher M.; Chu, Constance R.; Horvath, Steve; Qi, Lei S.; Bhutani, Nidhi; Rando, Thomas A.; et al. (Nature communications, 2020)
Aging is characterized by a gradual loss of function occurring at the molecular, cellular, tissue and organismal levels. At the chromatin level, aging associates with progressive accumulation of epigenetic errors that eventually lead to aberrant gene regulation, stem cell exhaustion, senescence, and deregulated cell/tissue homeostasis. Nuclear reprogramming to pluripotency can revert both the age and the identity of any cell to that of an embryonic cell. Recent evidence shows that transient reprogramming can ameliorate age-associated hallmarks and extend lifespan in progeroid mice. However, it is unknown how this form of rejuvenation would apply to naturally aged human cells. Here we show that transient expression of nuclear reprogramming factors, mediated by expression of mRNAs, promotes a rapid and broad amelioration of cellular aging, including resetting of epigenetic clock, reduction of the inflammatory profile in chondrocytes, and restoration of youthful regenerative response to aged, human muscle stem cells, in each case without abolishing cellular identity. Aging involves gradual loss of tissue function, and transcription factor (TF) expression can ameliorate this in progeroid mice. Here the authors show that transient TF expression reverses age-associated epigenetic marks, inflammatory profiles and restores regenerative potential in naturally aged human cells.